Comparative environmental footprint analysis of ultra-high-performance concrete using Portland cement and alkali-activated materials - Glanz, Dilan; Sameer, Husam; Göbel, Daniela; Wetzel, Alexander; Middendorf, Bernhard; Mostert, Clemens; Bringezu, Stefan (Frontiers in Built Environment, 2023)
Considering the ambitious greenhouse gas (GHG) emissions reduction and efficient use of resources targets set by the Sustainable Development Goals (SDGs) and the and the importance of concrete structures to achieve these goals, there is an increasing need to study the environmental performance of different concrete production alternatives. Cement is one of the main building materials that contribute significantly to global warming, therefore studying the environmental performance of innovative binders that can substitute the use of cement is highly recommended. This article investigates the climate, material, energy and water footprints of four innovated mixtures of ultra-high performance concrete (UHPC) with binder made of alkali-activated materials (AAM) in comparison with one made of Portland cement. Footprint analysis is done within cradle-to-grave life cycle assessment (LCA) boundaries. Within LCA the functional unit (FU) defines the quantification of the final product or service. The functional units of the UHPC were adapted for comparability of concrete mixtures with different compressive strength. The results show that UHPC made with AAM has 32% up to 45% better performance in terms of climate and 19% to 33% better performance in terms of material footprints, whereas trade off can be seen regarding 44% up to 83% higher energy footprints and 75% up to 146% higher water footprints. The disadvantages in energy and water footprints originate from the use of water glass. When allocation is considered, mixtures with high silica fume content perform worse in terms of their environmental footprints.